2012
DOI: 10.3109/14767058.2012.703726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standardized counseling on patient knowledge about induction of labor

Abstract: Standardized counseling improves patient knowledge about induction of labor. In the future, this information can be used to appropriately direct patients' expectations and improve satisfaction with the induction process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…19 Complications such as cord prolapse and placental abruption are uncommon. 28,29 The above studies indicate that information about risk in postterm pregnancy and the medical advantages of IOL is needed. Furthermore, the results of the few existing studies are ambiguous.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Complications such as cord prolapse and placental abruption are uncommon. 28,29 The above studies indicate that information about risk in postterm pregnancy and the medical advantages of IOL is needed. Furthermore, the results of the few existing studies are ambiguous.…”
mentioning
confidence: 99%
“…23,26,27 Thus, there is a need for continued strategies to facilitate women's involvement in decision making to support a good birth experience. 28,29 The above studies indicate that information about risk in postterm pregnancy and the medical advantages of IOL is needed.…”
mentioning
confidence: 99%
“…In a study involving two groups of women who were being prepared for induction of labour, one group was counselled using a standard counselling tool and the other was counselled using a non-standard tool. The study indicated the first group had a better knowledge and understanding about the procedure, even though outcome of the procedure had no direct relation to their understanding [ 31 ].…”
Section: Discussionmentioning
confidence: 99%